Limbal Epithelial and Mesenchymal Stem Cell Therapy for Corneal Regeneration. (3rd March 2020) - Shukla, Sachin; Shanbhag, Swapna S; Tavakkoli, Fatemeh; Varma, Shobhit; Singh, Vivek; Basu, Sayan
ABSTRACT: Corneal pathologies are a major cause of blindness and visual impairment, especially in the developing world. However, not only is there a global shortage of donor corneal tissue, but a significant proportion of these blinding pathologies also carry an unfavourable long-term prognosis for conventional corneal transplantation. In the last few decades, there has been a spurt of research on developing alternate approaches to address corneal blindness, including stem cell therapy. After the discovery of epithelial stem cells at the limbus, successful cell-based approaches to treat severe ocular surface disease were developed and have subsequently become widely practised across the world. More recently, mesenchymal stem cells were identified near the epithelial stem cells at the limbus, providing a unique opportunity to develop regenerative therapies for both corneal epithelial and stromal pathologies. This review firstly emphasises on qualifying limbal stem cells as either epithelial or mesenchymal and then summarises all the existing knowledge on both cell types and their individual roles in corneal regeneration. The review describes the history, indications, techniques, and outcomes of the different methods of limbal epithelial stem cell transplantation and elaborates on the potential applications of limbal mesenchymal stem cell therapy.